Beyond Neoliberalism : Social Analysis after 1989 - Burchardt, Marian; Kirn, Gal (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book explores how changes that occurred around 1989 shaped the study of the social sciences, and scrutinizes the impact of the paradigm of neoliberalism in different disciplinary fields. The contributors examine the ways in which capitalism has transmuted into a seemingly unquestionable, triumphant framework that globally articulates economics with epistemology and social ontology. The volume also investigates how new narratives of capitalism are being developed by social scientists in order to better understand capitalism's ramifications in various domains of knowledge. At its heart, Beyond Neoliberalism seeks to unpack and disaggregate neoliberalism, and to take readers beyond the analytical limitations that a traditional framework of neoliberalism entails.
Keywords: Social sciences.; Social structure.; Social inequality.; Sociology.; Social sciences -- Philosophy.; elektronické knihy; electronic books